2014
DOI: 10.1007/s10072-014-1937-8
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors’ neuroprotective effect against glutamate-induced neurotoxicity

Abstract: Glutamate is the most abundant excitatory brain neurotransmitter that has important functional significance with respect to neurodegenerative conditions. Glutamate-mediated excitotoxicity and neurodegeneration in Alzheimer's disease (AD) has been gradually becoming elucidated recently. Excessive release of glutamate induces an increase in intracellular Ca(2+) levels, thus triggers a cascade of cellular responses, ultimately leading to neuronal cell death. This type of neuronal damage induced by over-excitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 41 publications
0
16
1
1
Order By: Relevance
“…The neurotoxic effect of some xenobiotics result from changes in the brain expression of estrogen receptors, especially a decrease in nuclear ERβ and membrane GPR30 and, in consequence, inhibition of estrogen's neuroprotective action (Lan et al 2014;Lebesgue et al 2009;Lee et al 2012;Zhang et al, 2018). In the present study, a decrease in the mRNA level of all ER subtypes in the frontal cortex was observed, but there were no changes at the protein level either in the frontal cortex or in the hippocampus.…”
Section: Discussioncontrasting
confidence: 52%
“…The neurotoxic effect of some xenobiotics result from changes in the brain expression of estrogen receptors, especially a decrease in nuclear ERβ and membrane GPR30 and, in consequence, inhibition of estrogen's neuroprotective action (Lan et al 2014;Lebesgue et al 2009;Lee et al 2012;Zhang et al, 2018). In the present study, a decrease in the mRNA level of all ER subtypes in the frontal cortex was observed, but there were no changes at the protein level either in the frontal cortex or in the hippocampus.…”
Section: Discussioncontrasting
confidence: 52%
“…levels that triggers a cascade of cellular responses, leading to neuronal cell death, as mentioned before (Fig. 4) (Lan et al 2014).…”
Section: Changes In Glutamatergic and Dopaminergic Pathwaysmentioning
confidence: 97%
“…This increase may counteract the release and injurious effects of excitatory neurotransmitters, such as glutamate, via activation of the adenosine A 1 receptors, decreasing the release of neurotransmitters and depressing the neuronal activity in the CNS [70,71]. Glutamate is the most abundant excitatory neurotransmitter and may be potently toxic since the excessive release of glutamate could induce cell death via excitotoxicity [72,73]. Furthermore, it is described that glucocorticoids may increase the accumulation of glutamate, stimulate the N-methyl-D-aspartate (NDMA) receptors, and increase cytosolic intracellular Ca 2+ in postsynaptic neurons that activate various processes leading to neuronal death [74,75].…”
Section: Discussionmentioning
confidence: 99%